Developing a taxonomy of consumer preferences for enhancing B2C e-commerce last-mile delivery: fashion products - Shahdzah Wati Binte Adam (Nanyang Technological University, 2022)
With e-commerce, the trend that consumers are purchasing online is ever-increasing for most sectors. In particular, the fashion industry has been a large commercial activity in Singapore and this sector is set to flourish in the coming years. With e-commerce, fashion consumers are demanding more from retailers in terms of service level. As a result, the last-mile distribution of consumer goods from retailers plays a vital role in ensuring a seamless and enjoyable shopping experience. Two modes are applicable within Singapore’s fashion industry: Home Delivery and Collection In-Store. As consumers are heterogenous, they showcase a preference for a certain delivery mode for their online purchases. However, research relating fashion consumer characteristics with delivery mode and its attributes is minimal. Hence, the purpose of this report is twofold. It aims to identify (1) the preferred delivery option for fashion consumers in Singapore and (2) the delivery attribute they value the most. A stated choice experiment was conducted and the report adopted Hybrid Choice Model to include fashion lifestyles as latent variables. The results show that fashion consumers prefer home deliveries over collection in-stores. Fashion consumers consider delivery fees and lead time when deciding on a delivery option. Other delivery attributes like delivery reception (delivery day and time slot), return policy, travel distance and pickup location are insignificant for Singaporean fashion consumers. Moreover, the delivery mode choice is significantly associated with latent variables “Fashion-Conscious”, “Environmentally Conscious”, “Brand Conscious”, and “Economical Oriented”. This report offers insights for fashion retailers on which aspects of their delivery operations they should focus more to enhance customer satisfaction.